2021
DOI: 10.1111/evj.13498
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdominal dehiscence following laparotomy: A multicentre, international retrospective study

Abstract: Background: Incisional complications are a common cause of morbidity following laparotomy. Although uncommon, acute abdominal dehiscence (AAD) is a potentially fatal post-operative complication. However, few AAD cases are described in the literature. Objectives:To describe common features of cases of AAD following ventral midline laparotomy, management and outcomes. Study design: Retrospective case series.Methods: Hospital records of horses that underwent a ventral midline laparotomy at nine hospitals in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Evisceration of the abdominal contents can be a fatal event in horses and has been recorded following castration (Moll et al, 1995), due to acute abdominal dehiscence of a ventral laparotomy incision (Hann et al, 2022) or subsequent to penetrating abdominal wounds (Netto et al, 2006). Prognosis for survival decreases with increasing time, deteriorating condition of the horse, length of intestine eviscerated, intestinal damage or contamination and the requirement for intestinal resection anastomosis (Thomas et al, 1998; Van der Velden, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Evisceration of the abdominal contents can be a fatal event in horses and has been recorded following castration (Moll et al, 1995), due to acute abdominal dehiscence of a ventral laparotomy incision (Hann et al, 2022) or subsequent to penetrating abdominal wounds (Netto et al, 2006). Prognosis for survival decreases with increasing time, deteriorating condition of the horse, length of intestine eviscerated, intestinal damage or contamination and the requirement for intestinal resection anastomosis (Thomas et al, 1998; Van der Velden, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Evisceration of the abdominal contents can be a fatal event in horses and has been recorded following castration (Moll et al 1995), due to acute abdominal dehiscence of a ventral laparotomy incision (Hann et al 2022) or subsequent to penetrating abdominal wounds (Netto et al 2006). Prognosis for survival decreases with increasing time, deteriorating condition of the horse, length of intestine eviscerated, intestinal damage or contamination, and the requirement for intestinal resection anastomosis ( Van der Velden 1988;Thomas et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Infection of the incision adds expenses, extends hospitalisation and serves as a risk factor for further complications; including dehiscence and hernia formation (French et al, 2002; Honnas & Cohen, 1997; Ingle‐Fehr et al, 1997; Mair & Smith, 2005; Smith et al, 2007). These additional complications can in turn negatively affect future athletic performance and even survival (Davis et al, 2013; Hann et al, 2022).…”
Section: Surgical Site Infectionmentioning
confidence: 99%
“…According to one study, on a small number of horses, draught breeds were found at increased risk for AAD (Gardner & Mudge, 2017). Recently, however, a thorough, multicentric retrospective study was published (Hann et al, 2022). Hann et al reported that contrary to previous assumptions, AAD is not typically preceded by peritoneal fluid leakage from the incision (occurred in only 5% of cases), or by post‐operative colic or violent recovery (occurred in 24% of cases) (Hann et al).…”
Section: Incisional Dehiscencementioning
confidence: 99%
See 1 more Smart Citation